Evaluation of spray-dried eggs as a micronutrient-rich nutritional supplement - Pirkwieser, Philip; Grosshagauer, Silke; Dunkel, Andreas; Pignitter, Marc; Schneppe, Bernard; Kraemer, Klaus; Somoza, Veronika (Frontiers in Nutrition, 2022)
Regular consumption of hen eggs can help to prevent deficiencies of essential nutrients, such as essential amino acids, vitamin A and E or trace elements zinc and selenium, for vulnerable populations. This study focused on assessing the nutritional value of spray-dried eggs, favored by their manufacturability, storability and ease of addition to (complementary) foods. Using a wide range of analytical techniques, we recorded and compared the nutrient profiles of commercially produced pasteurized whole eggs and their respective powder samples spray-dried at 160 °C. Important nutrients that were not significantly affected by spray-drying include total fat content, several amino acids, α- and δ-tocopherol, lutein, zeaxanthin, essential trace elements and cobalamin. The most notable mean losses were found for unsaturated fatty acids, e.g. linoleic (by -38.7%, from 4.11±0.45 to 2.52±0.75 g/100 g DM) and linolenic acid (by -60.8%, from 0.76±0.05 to 0.30±0.04 g/100 g DM). Despite recording significant retinol losses in two out of three batches, the overall low reduction of -14% recommend spray-dried eggs as a valuable source of vitamin A. A daily intake of spray-dried egg powder corresponding to one medium sized egg meets dietary reference values for children, e.g. by 100% for vitamin E, by 24% for retinol, by 61% for selenium and by 22% for zinc. In conclusion, even though a dry weight comparison favors supplementation with pasteurized whole eggs, our results demonstrate a high potential for spray-dried eggs as nutritional supplement. However, the spray-drying process should be optimized towards higher retentions of unsaturated fatty acids and retinol.